Optically switchable transistors comprising a hybrid photochromic molecule/n-type organic active layer1. Issue 16 (28th April 2015) - Börjesson, K.; Herder, M.; Grubert, L.; Duong, D. T.; Salleo, A.; Hecht, S.; Orgiu, E.; Samorì, P.
<x xml:space="preserve">Abstract</x> Photoswitchable transistors based on a blend of an n-type fullerene derivative and a photochromic diarylethene can be gated either through the gate electrode or by photoisomerization of the diarylethene molecules.